A study to determine motivation factors that influence small farmers to become agriculture entrepreneurs via Gerai Buah-Buahan Segar FAMA / Amal Ridhuan Abdul Hadi - Abdul Hadi, Amal Ridhuan (Faculty of Business and Management, 2010)
The purpose of this research is to study the influence of human motivation involved in the agriculture entrepreneur’s process. This study is to better understand the motivation factors that influence small farmers to become agriculture entrepreneurs. This research is hoped to enhance the previous researches regarding motivation factors that influence not only agriculture entrepreneurs but also type of entrepreneurs. Motivations influence the decisions to grab opportunities, open up willingness to accept risks, and exploitation of resources, and that variance across people in these motivations will influence who pursues entrepreneurial opportunities, who assembles resources, and how people undertake the entrepreneurial process. This research is conducted on ‘Gerai Buah-Buahan Segar’ (GBBS) FAMA participants in Selangor. The respondents are all small farmers that had become agriculture entrepreneurs under the administration of FAMA. Self-administered questionnaires are distributed of this research. The sample used for this research is respondents of Gerai Buah-Buahan Segar’ (GBBS) FAMA state of Selangor, Negeri Sembilan and Melaka. The sample size studied is 50 respondents and the researcher has adopted the descriptive research design because it uses to describe something such as groups like local community. This study used the descriptive research design through personal interview method.